Evaluation of Electric Power Saving Due to Oil Slime Cleaning in Linear Part of Oil Pipeline - V. A. Anischenko; N. V. Tokochakova; А. S. Fikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
The paper presents evaluation method of electric power saving due to periodical cleaning of oil pipeline linear part which is intended to increase an equivalent diameter of the pipeline. The proposed method is based on statistical model developed on the basis of 24-hourly statistics reflecting modes of electric power consumption that take place at an enterprise. Electric power saving is evaluated according to changes of an equivalent diameter in the process of oil pipeline cleaning (and after this process) with respect to changes of an equivalent diameter without pipeline cleaning.